Extending Jenkins : get a complete walkthrough of the many interfaces available in Jenkins with the help of real-world examples to take you to the next level /: get a complete walkthrough of the many interfaces available in Jenkins with the help of real-world examples to take you to the next level. (2015) - Simpson, Donald
No abstract available